Less Anti-infliximab Antibody Formation in Paediatric Crohn Patients on Concomitant Immunomodulators. Issue 4 (October 2017) - Kansen, Hannah M.; van Rheenen, Patrick F.; Houwen, Roderick H.J.; Tjon A Ten, Walther; Damen, Gerard M.; Kindermann, Angelika; Escher, Johanna C.; Wolters, Victorien M.
ABSTRACT: Objectives: To evaluate the effect of immunomodulators on formation of antibodies to infliximab (ATI) in paediatric patients with Crohn disease (CD) and the association of ATI and loss of response. Methods: Retrospective multicentre observational study (January 2009–December 2014) among Dutch children with CD treated with infliximab (IFX). ATI formation was analysed with Chi-square test and time-to-ATI formation with Kaplan-Meier and log-rank test. Results: A total of 229 children were identified. ATIs were measured in 162 patients (70.7%) and 25 (15%) developed ATIs: 6 of 62 (10%) on continuous combined immunosuppression (CCI), 11 of 81 (14%) on early combined immunosuppression (ECI), and 8 of 19 (42%) on IFX monotherapy. ATI formation was higher in patients on IFX monotherapy compared to CCI ( P = 0.003) and ECI ( P = 0.008), whereas no significant difference was found between CCI and ECI. Sixteen out of 25 patients (64%) with ATIs had loss of response, compared with 32 of 137 patients (19%) without ATIs ( P < 0.00002, log rank 0.02). Among patients treated with ECI, 10 of 55 (18%) developed ATIs within the first 12 months, compared to 1 of 26 (4%) after more than 12 months. Conclusions: In children with CD combination therapy is associated with significant reduction of antibody formation and prolonged effectivity compared to IFX monotherapy. ECI for at least 12 months, followed by IFX monotherapy, may be an equally effective alternative to CCI. Abstract : Supplemental Digital Content is available in the text